ANALYSIS AND IDENTIFICATION OF DAMAGE TO AMC 36-800/MA AN SHAN LATHES USING FAILURE MODE AND EFFECT ANALYSIS AND FAULT TREE ANALYSIS METHODS - Fuad, Achmad Nur; Hidayat, Hidayat; Rizqi, Akhmad Wasiur (JTI: Jurnal Teknik Industri, 2024)
Maintenance emerges as a crucial intervention to ensure the sustained reliability of machinery. The AMC 36-800/MA AN SHAN lathe, a piece of equipment subject to extensive operational demands, frequently encounters breakdowns, thereby obstructing the seamless execution of maintenance activities for facilities. This investigation seeks to pinpoint the components responsible for the failures and malfunctions afflicting the lathe above. Employing the methodologies of Failure Mode and Effects Analysis (FMEA) and Fault Tree Analysis (FTA), this study successfully identifies the components at the epicentre of the machine's vulnerabilities. The analysis culminates in delineating critical components by calculating Risk Priority Numbers (RPN), unveiling a pivotal RPN value of 309.57. Moreover, it isolates two components whose failure modes surpass the critical RPN threshold: the Drive Motor and the Fixed Head. The genesis of these failures can be attributed to the escalating operational intensity, elevated engine temperatures, and a maintenance regimen that is both sporadically scheduled and suboptimal. Keywords: Lathe AMC 36-800/Ma AN Shan, Failure mode, FMEA, FTA, RPN